Hyperviscosity and Rouleaux Formation in Waldenstrom Macroglobulinemia - Ishan Kirti; Bargas Alkhzouz; Iyanu Olateju; Jeffrey Iding; Deepty Bhansali; Christopher J. Haas (Annals of Internal Medicine: Clinical Cases)
Waldenstrom macroglobulinemia is a distinct lymphoproliferative disorder resulting in excess production of IgM. Excess IgM and its subsequent pentameric formation may lead to the development of rouleaux and the hyperviscosity syndrome, an oncologic emergency typified by the presence of neurological changes. Plasmapheresis remains the therapy of choice for patients with the hyperviscosity syndrome, marked elevation of serum IgM, or serum viscosity, even in the absence of symptoms.